An Example of Reparatory Surface Welding of the Mining Machine Vital Part - Dušan Arsić; Ružica Nikolić; Vukić Lazić; Srbislav Aleksandrović; Ljubica Radović; Nada Ilić; Branislav Hadzima (Communications - Scientific letters of the University of Zilina, 2021)
Mining machines’ components, or the whole structure, are prone to frequent premature damages and fractures what is explained either by inadequate design and construction or by insufficient knowledge of the material’s and welded joints’ properties and oversights in manufacturing. Here is considered the bucket-wheel excavator, i.e. the fracture of the tooth of the girth gear, which enables the circular motion of the excavator’s upper structure (which was in operation for 5000 hours). The gear was made of the cast steel GS 40 MnCrSi3 V. The reparatory hard-facing (HF) technology of the fractured tooth required specification of numerous operations including the preparation works. The reparation realized the two-fold savings, in time and money - the new girth gear costs over 500 000 € and its manufacturing lasts 6 to 9 months, while the safety and quality of the repaired tooth was guaranteed.